2014
DOI: 10.2478/s11686-014-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of different genetic markers for the detection of Acanthamoeba spp. isolates

Abstract: Acanthamoeba are widespread free-living amoebae which may cause granulomatous amoebic encephalitis (GAE), keratitis, skin ulcerations and disseminated tissue infection. An important diagnostic and prognostic factor for the treatment of infection is a quick and correct diagnosis of amoebae strains. The aim of our study was to develop a rapid method for detection and identification of pathogenic Acanthamoeba spp. strains from diagnostic material collected from water. In this study we analysed five amplification-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In Poland, free-living amoebae have been isolated from waters in the vicinity of Poznań [ 43 ]. Successively, in further environmental studies on Acanthamoeba , potentially pathogenic strains have been detected in Lake Żarnowieckie, the Piaśnica River, and a canal used as a recreational resort in northern Poland; moreover, free-living amoebae have been isolated from natural water bodies including lakes, ponds, rivers, and lagoons of the West Pomeranian and Lubuskie area, in tap water of the water supply system of Szczecin city, in surface water layers, and in water with sediment in northern Poland at the area of the cities Gdańsk, Gdynia, and Sopot, as well as in swimming pools and fountains in western Poland [ 44 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Poland, free-living amoebae have been isolated from waters in the vicinity of Poznań [ 43 ]. Successively, in further environmental studies on Acanthamoeba , potentially pathogenic strains have been detected in Lake Żarnowieckie, the Piaśnica River, and a canal used as a recreational resort in northern Poland; moreover, free-living amoebae have been isolated from natural water bodies including lakes, ponds, rivers, and lagoons of the West Pomeranian and Lubuskie area, in tap water of the water supply system of Szczecin city, in surface water layers, and in water with sediment in northern Poland at the area of the cities Gdańsk, Gdynia, and Sopot, as well as in swimming pools and fountains in western Poland [ 44 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study confirmed the usefulness of PCR for the early, rapid, and sensitive diagnosis of pathogenic Acanthamoeba spp. strains (Derda et al 2014 ). The best highly specific marker that distinguishes pathogenic Acanthamoeba strains in water samples in Poland is a pair of primers of Aca 16.…”
Section: Discussionmentioning
confidence: 99%